2004
DOI: 10.1111/j.1365-4632.2004.02371.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of health‐related quality of life in women with severe facial blemishes

Abstract: Severe facial blemishes of any cause have a significant impact on women's QOL, and the effect of these lesions is mediated in part by psychological characteristics related to self-perception and self-presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 18 publications
0
55
0
5
Order By: Relevance
“…Currently, Melasma therapy includes opaque anti-UVA and anti-UVB sunscreen such as zinc oxide, a variety of bleach gels, cream (3-11), Hydroquinone compounds, lowdensity steroids, kojic acid, Arbotin, azelaic acid, AHA, and retinoid (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Administration of topical tretinoin gel is often required, too.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, Melasma therapy includes opaque anti-UVA and anti-UVB sunscreen such as zinc oxide, a variety of bleach gels, cream (3-11), Hydroquinone compounds, lowdensity steroids, kojic acid, Arbotin, azelaic acid, AHA, and retinoid (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Administration of topical tretinoin gel is often required, too.…”
Section: Discussionmentioning
confidence: 99%
“…The onset of Melasma is often between 30 and 55 years of age (5). As Melasma is seen in exposed areas of the skin, particularly the face, it affects the quality of life as well as the self-confidence of the patients (6). By studying Iranian traditional medicine books, it has been shown that "Kalaf ", in which parts of the skin on the face darkens, is known as Melasma in contemporary medicine (7).…”
Section: Introductionmentioning
confidence: 99%
“…Conclusions: Considering the anti-melanogenic activity and human safety, CCE is considered as a potential anti-melanogenic agent and may be effective for topical application for treating hyperpigmentation disorders. and accumulation of melanin in the skin could be a serious skin disorder and aesthetic problems, which are decreasing social functioning, reducing productivity at work or school, and lowering the self-esteem of patients [3][4][5][6] . Melanogenesis is regulated by various environmental, hormonal and genetic factors, including α-melanocyte stimulating hormone, theophylline, cAMP-elevating agents, and estrogen, and UV light.…”
Section: P E E R R E V I E W Abstract Abstractmentioning
confidence: 99%
“…Cellular tyrosinase activity was measured by the method of Yen (1) rutin, (2) narirutin, (3) naringin, (4) hesperidin, (5) neohesperidin, (6) neohesperidin dihydrochalcone, (7) naringenin, (8) hesperetin, (9) aprgrnin, (10) nobiletin, (11) tangeretin, (12) auraptene was diluted with ethanol to obtain a series concentration of working solutions, and subjected to HPLC analysis.…”
Section: Determination Of Cellular Tyrosinase Activitymentioning
confidence: 99%
“…In fact, for the last century, both social and emotional impact, diminished self-esteem and psychiatric comorbidities have been reported to occur in these patients. [9][10][11][12] They have been described as immature, anxious, with diminished self-esteem and feelings of guilt and shame, 13,14 or as psychoneurotic, with hysterical or obsessive-compulsive configurations. 15 In the present study we intended to explore and draw conclusions on the psychopathologic distress experienced by Portuguese rosacea patients as compared to a group of dermatological patients suffering from acute, non-conspicuous, accidental dermatoses.…”
Section: Introductionmentioning
confidence: 99%